2021
DOI: 10.1021/acs.macromol.1c02103
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Insights into Free-Radical Polymerization in the Presence of Catechols and Catechol-Functionalized Monomers

Abstract: Polymers containing catechols are attractive for use in a diverse range of applications. However, the direct incorporation of catechols is challenging in polymers produced by radical polymerization due to transfer and termination reactions that readily occur between catechols and radical species. In this work, it is demonstrated that while monosubstituted olefins such as styrene and methyl acrylate readily undergo chain transfer to phenolic hydrogens, methacrylic monomers do not suffer any inhibitory activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Recent studies have shown that polar solvents with a strong hydrogen bonding ability to phenol groups could prevent side reactions of catechol in radical polymerizations. This allows for the synthesis of copolymers with dopamine side chains without requiring any protection for diol groups. , In this study, RAFT polymerization was employed to synthesize a novel adhesive and conductive bioinspired copolymer p­(METAC-DMA), as shown in Figure a. This biocompatible and multifunctional copolymer possessed adhesive and conductive properties due to its appropriate functional units (dopamine and choline), which can be combined with any biopolymers containing amine groups in an oxidative environment to form conductive and bioadhesive hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that polar solvents with a strong hydrogen bonding ability to phenol groups could prevent side reactions of catechol in radical polymerizations. This allows for the synthesis of copolymers with dopamine side chains without requiring any protection for diol groups. , In this study, RAFT polymerization was employed to synthesize a novel adhesive and conductive bioinspired copolymer p­(METAC-DMA), as shown in Figure a. This biocompatible and multifunctional copolymer possessed adhesive and conductive properties due to its appropriate functional units (dopamine and choline), which can be combined with any biopolymers containing amine groups in an oxidative environment to form conductive and bioadhesive hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…We observe the key difference in the required reaction time between additions of indene and phenylmaleimide is from an extended induction period which we attribute to oxygen-containing inhibiting species (specifically those which operate via chain transfer) generally being more effective on electron-rich monomers than those that are electron-deficient. 44 We hypothesise that such species would form upon generating hydrogen peroxide from the reaction of singlet oxygen (generated from the catalyst) with ascorbic acid. However, we have not confirmed these species (or even the presence of hydrogen peroxide) spectroscopically.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study indicated that catechol OH groups are protected by hydrogen bonding with DMF. 16 We believe this “on-demand protection” enables control of the RAFT polymerization of unprotected DOPAm. Subsequently, the polymer obtained after 360 min was purified by reprecipitation and characterized by 1 H NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%